Grammar dictionary: designing and structuring issues - Avetisyan, Yuri (Bulletin of Yerevan University B: Philology, 2022)
The article briefly describes the main components of the design and structure of the "Modern Armenian Educational Grammar Dictionary". A complete grammatical description of about 4000 words will be illustrated in the dictionary. It should be presented to users in two formats: printed and electronic.The dictionary has a morphological-structural character; it will present the morphological description of the word unit of Мodern Eastern Armenian. The syntactic features of the word form will be given only to the degree that they are related to the word formation. The dictionary will have a normative significance, indicating the possible ways of language development. The dictionary will also present part-of-speech variations, typical examples of the case and conjugation patterns of verbal units, and the stylistic value of words.
Keywords: grammar dictionary; electronic; morphological; complete; educational; description; displacements; potential forms; typical example; normalization; variation